Overview of the genus Sympodium Ehrenberg, 1834 (Octocorallia, Alcyonacea, Xeniidae), with the description of new species, revealing regional endemism - Benayahu, Yehuda; Ekins, Merrick; Mcfadden, Catherine S. (Zootaxa, 2021)
The oldest existing type material for any of the xeniid soft corals, Sympodium caeruleum Ehrenberg, 1834, is re-described. An integrated analysis of molecular and morphological characters of Indo-Pacific Xeniidae support the description of seven new species of that genus. The extent of interspecific morphological variation within the genus is extensive; colonies arise from an encrusting membrane of variable thickness that can be either mat-like or may have ribbon-like extensions or irregularly shaped low mounds. The polyps can either arise separately from the membrane or may be arranged into clusters of polyps that bud off at different levels to form small branched groups. The sclerites of all species are uniformly ellipsoid platelets, abundant throughout the colony. The genetic results suggest that Sympodium species demonstrate restricted geographic ranges and regional endemism, with distinct genotypes (molecular operational taxonomic units) each mostly found at a single Indo-Pacific location. The results emphasize the importance of integrating classical taxonomy with a re-examination of original old type material and molecular phylogenetic analyses, in order to delineate species boundaries and to recognize biodiversity patterns.